2002
DOI: 10.1046/j.1523-1755.2002.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxalate on the re-initiation of DNA synthesis in LLC-PK1 cells do not involve p42/44 MAP kinase activation

Abstract: These findings demonstrate that oxalate does not activate the p42/44 MAP kinase pathway, and the effects of oxalate are mediated by pathways that are distinct from those of EGF, PDGF and insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Though the functional significance of KIM-1 shedding is not known, Mitogen Activated Protein Kinases, especially ERK and p38 MAPK, have been shown to play an important role in this process [32]. Previous studies in our laboratory have identified activation of p38 MAPK in kidney epithelial cells exposed to Oxalate and COM-Crystals [7], [8], [17]. Based on these observations, it is tempting to speculate that signaling by p38 MAPK pathway may also play an important role in KIM-1 overexpression and shedding during hyperoxaluria mediated tubular injury, however, additional studies are need to support such conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…Though the functional significance of KIM-1 shedding is not known, Mitogen Activated Protein Kinases, especially ERK and p38 MAPK, have been shown to play an important role in this process [32]. Previous studies in our laboratory have identified activation of p38 MAPK in kidney epithelial cells exposed to Oxalate and COM-Crystals [7], [8], [17]. Based on these observations, it is tempting to speculate that signaling by p38 MAPK pathway may also play an important role in KIM-1 overexpression and shedding during hyperoxaluria mediated tubular injury, however, additional studies are need to support such conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…It is worthwhile to mention here that the previous study (10) from our laboratory has shown that the effects of oxalate and fetal bovine serum on the DNA synthesis were additive, suggesting involvement of independent signaling pathways in oxalate and fetal bovine serumstimulated DNA synthesis. These observations were further confirmed by evaluating the effects of various growth factors alone or in combination with oxalate on the re-initiation of DNA synthesis (73). The fact that oxalate induces re-initiation of the DNA synthesis without activating p42/44 MAP kinase suggests that oxalate-induced re-initiation of the DNA synthesis in renal epithelial cells follows signal transduction pathways that are distinct from serum-and growth factor-stimulated DNA synthesis.…”
Section: Discussionmentioning
confidence: 69%
“…This unprecedented suppression of a large number of genes in renal epithelial cells suggests a program of the suppression of transcriptional activity. However, previous studies by have shown that the exposure of renal epithelial cells to oxalate results in the up-regulation of several genes [12], [15], [18], [20], [20], [22,23]. Thus, the notion of a general transcriptional repression is too simplistic of an explanation.…”
Section: Discussionmentioning
confidence: 98%